Perancangan Protokol Pegasis Untuk Aplikasi Sistem Absensi Sidik Jari - Rabil Kurniawan; Feri Candra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
WSN applications have been widely used in recent years. In a very complex wsn application, a routing protocol is mandatory for a WSN network system. Among the communication protocols that have been developed to date, hierarchical protocols are the most widely used type of routing. PEGASIS is one of the many types of protocols that apply the hierarchcal protocol principle. In this study, the PEGASIS protocol will be implemented on the Arduino platform for the fingerprint attendance system, where NRF24L01 is used as the radio transceiver module. Testing of QoS in the form of packet loss, transfer speed, delay, power consumption and memory usage are indicators of the feasibility of this system. After testing, it was found that the delivery packet loss was 0%, the transfer speed ranged from 4.22 - 12.92 Kbps, the resulting delay was 2.92 - 5.54 ms. The power consumption of 23 devices a day is 463.49 Joules. From the results that have been obtained, the system developed is feasible to be implemented in a real way. Keywords: WSN, PEGASIS, QoS